Probe: Trump’s Ardent Male MAGA Supporters, and Walter J. Ong's Thought - Farrell, Thomas J. (New Explorations)

(untitled) (New Explorations Association, 2024)
On Tuesday, November 5, 2024, Americans will vote for the nest president of the United States. I plan to vote for vice President Kamal Harris to be the next president of the United States. But former president Donald Trump’s ardent male MAGA supporters plan to vote for him to the next president of the United States, because they feel under siege because of certain cultural developments in the United States over the last decade or so. In the present short “Probe,” I use the thought of the American Jesuit scholar Walter J. Ong to explain certain psychodynamics about our contemporary secondary oral culture that are contributing to Trump’s male MAGA supporters feeling under siege over the last decade or so.